1998
DOI: 10.1007/s11745-998-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific analysis of soybean triacylglycerols

Abstract: Thirty soybean germplasm lines representing a wide distribution of fatty acid compositions were analyzed stereospecifically by using a chiral column to resolve the sn-1 and sn-3 positions of glycerol. The amounts of each acyl group on each of the sn positions were plotted vs. the amount of that acyl group in the triacylglycerols (TAG), and the plots were fitted by linear regression. The deviation of individual data points from the linear regressions was much greater than observed in previous studies. This coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…This showed that as the total concentration in oil of a given unsaturated FA increased, its concentration at the sn-2 position also increased. The same relationship has been shown to exist for other oilseeds including soybean [23], maize [24], and Brassica species [25]. The few samples that deviated from this linear relationship had FA compositions markedly different from each other in respect of one or more unsaturated FA.…”
Section: Positional Distribution Of Fatty Acidssupporting
confidence: 60%
“…This showed that as the total concentration in oil of a given unsaturated FA increased, its concentration at the sn-2 position also increased. The same relationship has been shown to exist for other oilseeds including soybean [23], maize [24], and Brassica species [25]. The few samples that deviated from this linear relationship had FA compositions markedly different from each other in respect of one or more unsaturated FA.…”
Section: Positional Distribution Of Fatty Acidssupporting
confidence: 60%
“…Similar graphs and linear regression were made. Harper (23) found that there was little saturate at the sn-2 position, and that the slopes of this position for palmitate and stearate were 0.04 and 0.08, as compared with the sums of sn-1 and sn-3 slopes of 2.94 and 2.91. Thus, the sn-2 position palmitate and stearate in PL had greater slopes than in TG.…”
Section: Resultsmentioning
confidence: 98%
“…It is well documented that saturated fatty acids predominantly occupy the sn-1 and sn-3 positions of soybean TG, and these two positions reflected the saturated fatty acid change in oil (21)(22)(23). Harper (23) used soybean lines that had fatty acid composition ranges similar to those used in this study to analyze acyl group stereospecific distribution in TG.…”
Section: Resultsmentioning
confidence: 99%
“…The FA composition of the individual fractions and of the original TGs was determined by GLC and used to calculate the positional distribution on the glycerol backbone. Thirty soybean germplasm lines were analysed stereospecifically [246] by using the chiral column method of Takagi and Ando [243]. On a chiral Sumipax OA-4100 stationary phase an improved resolution of enantiomeric 1,2(2,3)-diacyl-sn-glycerols was obtained [247,248].…”
Section: Stereospecific Analysismentioning
confidence: 99%